Defining Quality of Life - Kassianos, Angelos P.; Tsounta, Stephanie (My University, 2022)
The definitions of quality of life (QoL) and health-related quality of life (HRQoL) are discussed in this chapter. The lack of consensus on defining concepts can lead to evidence that lack contextual validity and minimize their impact on research and health care. Since HRQoL is the primary or secondary endpoint in most cancer clinical trials and the interest in assessment during health care is growing, we present related definitions that can inform readers of this handbook on how to approach the evidence regarding the impact that cancer diagnosis and related therapies have on their lives.
Keywords: Clinical trials; Conceptualization; Definitions; Health-related quality of life; Quality of life; Well-being